participatory land use planning plup in rurual Cambodia (Phnom Penh, 2001)
This is provide information framework conditions, getting stared, steps and procedures of plup ( preparation of field work, situation analysis in the community, prreliminary identification and scrêning of options, ..) and PLUP under special conditions.